PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA LINGKUNGAN DAN NILAI PERUSAHAAN - IRVANIA PARLUPI, FATMA (Jurnal Akuntansi AKUNESA, 2018)
This study aims to examine the effect of corporate governance on environmental performance and firm value. Variable corporate governance were proxied by independent commissioners, managerial ownership, institutional ownership, and audit committee. This study used 95 sample data companies sectors plantation, mining, and manufacturing on the Indonesia Stock Exchanges during 2015-2017 period. This research uses quantitative approach with multiple linear regression as its method to analyze the data. The result showed that institutional ownership affect environmental performance. While, independent commissioners, managerial ownership, and audit committee does not affect environmental performance. Independent commissioner affect firm value. While, managerial ownership, institutional ownership, and audit committee does not affect firm value. Keywords : Corporate Governance, Environmental Performance, Firm Value